Causes and temporal changes in nationally collected stillbirth audit data in high-resource settings. Issue 3 (June 2017) - Norris, Tom; Manktelow, Bradley N.; Smith, Lucy K.; Draper, Elizabeth S.
Abstract: Few high-income countries have an active national programme of stillbirth audit. From the three national programmes identified (UK, New Zealand, and the Netherlands) steady declines in annual stillbirth rates have been observed over the audit period between 1993 and 2014. Unexplained stillbirth remains the largest group in the classification of stillbirths, with a decline in intrapartum-related stillbirths, which could represent improvements in intrapartum care. All three national audits of stillbirths suggest that up to half of all reviewed stillbirths have elements of care that failed to follow standards and guidance. Variation in the classification of stillbirth, cause of death and frequency of risk factor groups limit our ability to draw meaningful conclusions as to the true scale of the burden and the changing epidemiology of stillbirths in high-income countries. International standardization of these would facilitate direct comparisons between countries. The observed declines in stillbirth rates over the period of perinatal audit, a possible consequence of recommendations for improved antenatal care, should serve to incentivise other countries to implement similar audit programmes.